Implemetasi Pendidikan Lingkungan Dalam Mengelola Sampah Domestik Pada Masyarakat Di Marengan Laok Sumenep - Firdausi, Firdausi; Shulhan, Shulhan (IAIN PONOROGO, 2024)
To ensure that a village is said to be radiant, active involvement is needed between the village government and all elements of society. Marengan Laok Village is one of 9 villages in Sumenep Regency, claimed to be a slum village. Since 2017, the domestic waste problem has not been found; the government is said to be slow in dealing with the long-standing problem. It cannot be separated from people's lifestyles, which have shifted to using goods that are not environmentally friendly. This phenomenological research uses a case approach. Observations, interviews, and documentation were carried out to collect data. After analyzing the data using the constant comparative method, it was concluded that environmental education was not provided sustainably, so its implementation was stagnant. Even though they present experts, it does not guarantee changes in people's social behavior, such as prevention, healthy lifestyles, and recycling organic and inorganic waste. It is motivated by the unavailability of facilities, geographical location, and lack of knowledge, which makes people less concerned about the environment. Thus, the results of this education fail. However, behind this failure, the psychoeducation that teachers carry out from an early age on students can encourage children to protect the environment. The environmental saving program from INSTIKA Guluk-Guluk KKN students also increased citizens' awareness and positive behavior, such as reducing waste consumption, handling waste, and recycling domestic waste. By building this character, residents began to rise and try to improve their environment through waste laboratory containers.